A rare earth double-doped modified composite solid electrolyte and a preparation method thereof
Patent Information
- Application Number
- CN202611284369.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-24
- Publication Date
- 2026-10-23
AI Technical Summary
[0005]为了解决上纯相固态电解质低温晶格收缩、锂空位不足、界面副反应严重;单一稀土掺杂改性维度单一、掺杂利用率低;多元稀土无序掺杂晶格应力失衡、电荷失配、高温掺杂易析出杂相、高低温电导无法兼顾缺陷,开发一种稀土双掺杂改性复合固态电解质及制备方法,选用大半径La³⁺、小半径Y³⁺双稀土差异化位点协同掺杂,精准取代基体Zr4⁺、Li⁺晶格位点,分级调控晶胞体积、定向构建可控锂空位;配套微量锂源电荷补偿掺杂,平衡异价稀土取代晶格电荷,消除电荷缺陷捕获锂离子问题;采用低温机械力预掺杂+梯度退火锁存晶格缺陷工艺,全程最高热处理温度720℃,避免稀土析出、杂相生成,锁存掺杂活化位点;基体采用氧化物-卤化物复合基体,双稀土同步优化基体晶界稳定性、双向适配锂负极/高压正极界面,实现-60℃超低温高导锂、高力学抗枝晶、宽电化学窗口、低界面阻抗,工艺适配量产,掺杂均匀可控
[0029]1、双稀土差异化定点掺杂,同步解决高低温晶格失效问题:采用大半径La³⁺取代Zr位点、小半径Y³⁺填充锂间隙位点的分级掺杂设计,大半径稀土撑大晶胞自由体积,抑制-60℃极低温下晶格收缩塌陷;小半径稀土平衡晶胞内部应力,避免冷热循环产生晶格微裂纹,相较于单一稀土掺杂,可同时大幅提升常温与超低温离子电导率,彻底解决纯相电解质低温导电断崖衰减缺陷。
Smart Images

Figure CN122968417A_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of solid electrolyte technology, and in particular to a rare earth dual-doped modified composite solid electrolyte and its preparation method. Background Technology
[0002] Cubic LLZO garnet solid electrolytes possess a wide electrochemical window and high dendrite modulus, making them the mainstream system for solid-state lithium metal batteries. However, pure LLZO has significant drawbacks: at low temperatures, the lattice shrinks dramatically, lithium-ion channels close, and conductivity drops sharply; intrinsic lithium vacancies are scarce, and lattice defects easily trap lithium ions, resulting in low carrier migration efficiency; at the same time, the side reactions at both the lithium anode and the high-voltage cathode are intense, leading to persistently high interfacial impedance.
[0003] Existing single rare earth doping methods can only optimize the lattice in one direction, resulting in limited modification dimensions and low doping utilization. Traditional disordered multi-element rare earth high-temperature solid-state doping easily induces lattice stress imbalance and charge mismatch, leading to the precipitation of rare earth oxide impurities that block ion channels, making it difficult to achieve both high and low temperature conductivity. Conventional LLZO-halide simple compounding schemes lack targeted doping control, resulting in weak interphase bonding and easy reduction side reactions between halides and metallic lithium.
[0004] Existing modification schemes cannot simultaneously solve multiple problems such as low-temperature lattice failure, interface degradation, impurity phase precipitation, and high-temperature damage to halides during mass production. They are difficult to adapt to extreme low-temperature conditions such as high-altitude energy storage and vehicle-mounted applications. There is an urgent need for a new type of dual rare earth point-doped composite solid electrolyte scheme. Summary of the Invention
[0005] To address the shortcomings of pure-phase solid-state electrolytes, such as low-temperature lattice shrinkage, insufficient lithium vacancies, and severe interfacial side reactions; single rare-earth doping modification having limited dimensionality and low doping utilization; and multi-element rare-earth disordered doping resulting in lattice stress imbalance, charge mismatch, easy precipitation of impurities at high temperatures, and an inability to simultaneously achieve high and low temperature conductivity, a rare-earth dual-doped modified composite solid-state electrolyte and its preparation method were developed. This method utilizes the synergistic doping of large-radius La³⁺ and small-radius Y³⁺ rare-earth sites to precisely replace the Zr matrix. 4 The system utilizes ⁺ and Li⁺ lattice sites to hierarchically control cell volume and directionally construct controllable lithium vacancies. It also incorporates trace lithium source charge compensation doping to balance the substitution of lattice charges by heterovalent rare earth elements, eliminating the problem of lithium-ion capture due to charge defects. A low-temperature mechanical pre-doping + gradient annealing process is employed to lock in lattice defects, with a maximum heat treatment temperature of 720℃ throughout the process, preventing rare earth precipitation and impurity phase formation, and locking in doping activation sites. The matrix uses an oxide-halide composite matrix, with simultaneous optimization of matrix grain boundary stability by dual rare earth elements, and bidirectional adaptation to the lithium anode / high-voltage cathode interface. This achieves ultra-low temperature high lithium conductivity (-60℃), high mechanical resistance to dendrite formation, a wide electrochemical window, and low interfacial impedance, ensuring process adaptability for mass production and uniform, controllable doping.
[0006] On the one hand, this application provides a rare-earth dual-doped modified composite solid electrolyte, wherein the general formula of the solid electrolyte is:
[0007] Li 7+δ La x Y y Zr 2-x-y La3O 12 -Li3Cl6;
[0008] Among them, x=0.08~0.15, y=0.04~0.09, δ=0.12~0.25.
[0009] According to the present invention, a rare earth dual-doped modified composite solid electrolyte is provided, with x=0.12, y=0.06, and δ=0.18.
[0010] According to the present invention, a rare-earth dual-doped modified composite solid electrolyte comprises a ceramic inorganic matrix, dual rare-earth doped modified components, and a charge-compensating lithium source. The ceramic inorganic matrix is a cubic phase LLZO oxide and rare-earth chlorine halide composite matrix, wherein the general formula of the rare-earth chlorine halide is Li. 3-a La a Cl6.
[0011] The dual rare earth doped modified components include lanthanum rare earth salt and yttrium rare earth salt.
[0012] According to the present invention, a rare earth dual-doped modified composite solid electrolyte is provided, wherein the solid electrolyte further includes nano-alumina.
[0013] According to the present invention, a rare earth dual-doped modified composite solid electrolyte is provided, wherein the mass ratio of cubic phase LLZO oxide to rare earth chloride halide in the ceramic inorganic matrix is 7:3.
[0014] Secondly, the present invention provides a method for preparing the above-mentioned rare-earth dual-doped modified composite solid electrolyte, comprising the following steps:
[0015] A ceramic inorganic matrix is vacuum activated to obtain an activated matrix; wherein the ceramic inorganic matrix is a cubic phase LLZO oxide and rare earth chloride halide composite matrix;
[0016] The activated matrix is immersed in a rare earth impregnation solution for mechanical predoping to obtain a predoped intermediate; wherein the rare earth impregnation solution contains lanthanum rare earth salt, yttrium rare earth salt and charge-compensating lithium source;
[0017] The pre-doped intermediate was subjected to low-temperature spray drying to obtain the doped precursor powder;
[0018] The above-mentioned doped precursor powder was subjected to three-stage gradient low-temperature annealing to obtain annealed doped powder; wherein the three-stage gradient low-temperature annealing was gradually increased from 320℃ to 720℃.
[0019] According to the method for preparing rare earth dual-doped modified composite solid electrolyte provided by the present invention, the rare earth impregnation solution further contains nano-alumina.
[0020] According to the method for preparing rare-earth dual-doped modified composite solid electrolyte provided by the present invention, the three-stage gradient low-temperature annealing includes:
[0021] The first stage involves a heating rate of 2℃ / min, raising the temperature to 320℃ and holding it at that temperature for 90 minutes.
[0022] The second stage involves a heating rate of 1.2℃ / min, raising the temperature to 560℃, and holding the temperature for 130 minutes.
[0023] The third stage involves a heating rate of 0.8℃ / min, raising the temperature to 720℃, and then maintaining that temperature for 160 minutes.
[0024] The method for preparing rare-earth dual-doped modified composite solid electrolyte according to the present invention further includes:
[0025] The annealed doped powder is then subjected to dry constant pressure molding to obtain an electrolyte sheet.
[0026] The method for preparing rare-earth dual-doped modified composite solid electrolyte according to the present invention further includes:
[0027] The electrolyte sheet is subjected to low-temperature interface passivation post-treatment.
[0028] In summary, the present invention has at least one of the following beneficial technical effects:
[0029] 1. Differentiated site-specific doping with dual rare earth elements to simultaneously solve the problem of high and low temperature lattice failure: The hierarchical doping design adopts a large-radius La³⁺ to replace Zr sites and a small-radius Y³⁺ to fill lithium interstitial sites. The large-radius rare earth element expands the free volume of the unit cell and suppresses lattice shrinkage and collapse at extremely low temperatures of -60℃. The small-radius rare earth element balances the internal stress of the unit cell and avoids lattice microcracks caused by thermal cycling. Compared with single rare earth doping, it can significantly improve the ionic conductivity at both room temperature and ultra-low temperature, and completely solve the low-temperature conductivity cliff-like attenuation defect of pure phase electrolytes.
[0030] 2. A matching lithium source charge compensation system significantly improves the effective carrier concentration of lithium ions. To address the lattice charge imbalance problem caused by heterovalent rare earth doping: a charge compensation lithium source is introduced to balance the lattice charge, eliminate lithium ion trapping centers formed by lattice defects, and reduce ion migration resistance. Compared with the doping scheme without lithium compensation, the number of mobile lithium vacancies in the system is increased by 2.7 times, and the ionic conductivity is increased by more than double under the same doping amount, significantly improving the utilization rate of doping modification.
[0031] 3. Uniform and controllable rare earth doping with no inert impurity phase precipitation and significantly reduced grain boundary impedance: The combined preparation process of liquid phase impregnation, high-energy mechanical force pre-embedding, and gradient low-temperature annealing allows rare earth ions to be uniformly embedded in the crystal lattice sites, with only trace amounts of rare earth distributed at the grain boundaries to optimize interfacial conduction; it avoids the problems of rare earth segregation and inert impurity phase blockage of ion channels caused by traditional high-temperature solid-phase blending, resulting in a significant reduction in grain boundary impedance and a batch performance dispersion controlled within 4%.
[0032] 4. Low-temperature gradient annealing process, balancing doping effect and matrix structure integrity: The highest temperature of the entire heat treatment is only 720℃, which is far lower than the sintering temperature of traditional garnet electrolytes above 1000℃; the solvent removal, lattice site substitution and defect latching are completed in three stages of temperature control, which not only ensures the stable embedding of the two rare earth elements into the lattice, but also avoids the hydrolysis of halide components and the thermal decomposition of polymers, thus fully preserving the low-temperature lithium-ion transport channels of the electrolyte and making it suitable for oxide-halide composite matrix systems.
[0033] 5. Bidirectional optimization of electrode interface compatibility, taking into account the needs of both lithium metal anode and high-voltage cathode: Y³⁺ can passivate the reduction activity of electrolyte grain boundaries, block the reduction side reaction between halides and lithium metal, and inhibit the growth of LiCl insulating passivation layer and lithium dendrites; La³⁺ enhances the lattice's anti-oxidation ability, widens the electrochemical window to 4.9V, and is suitable for high-nickel ternary high-voltage cathode. A set of modified electrolytes can simultaneously reduce the interface impedance on both sides of the anode and cathode, solving the shortcoming of existing doped systems that can only optimize the interface on one side.
[0034] 6. Synergistic improvement in mechanical properties and ion conduction properties, suitable for cell molding and processing: Dual rare earth elements synergistically regulate grain size and grain boundary bonding strength, the electrolyte has both high Young's modulus and suitable toughness, and the porosity of the compression molding is ≤3.2%, making it less prone to cracking and breakage; ultra-thin electrolyte sheets can be prepared without adding a large amount of organic binder, which not only has excellent resistance to dendrite puncture, but is also suitable for large-scale dry compression production.
[0035] 7. Strong process versatility and low mass production threshold, adaptable to wide temperature range and multi-condition energy storage equipment: The entire process is completed in a low dew point / argon protection environment. The equipment has no special high-temperature sintering requirements, and the process can be continuously integrated into the solid electrolyte production line. The component ratio and annealing temperature range are adjustable. The modified electrolyte has a stable operating range of -60℃ to 720℃, which can be widely used in extreme low-temperature conditions such as high-altitude vehicle, aerospace, and polar energy storage, and has a wider range of industrial application scenarios. Attached Figure Description
[0036] Figure 1 This invention describes the microstructure characteristics of the rare-earth dual-doped modified composite solid electrolyte.
[0037] Figure 2 This is a comprehensive microscopic characterization diagram of the finished product of Embodiment 1 of the present invention. Detailed Implementation
[0038] The present application will be further described in detail below with reference to the accompanying drawings and embodiments.
[0039] This invention provides a rare-earth dual-doped modified composite solid electrolyte, which uses cubic phase LLZO oxide and rare-earth chlorine halides as the composite matrix. It is doped and modified by dual rare-earth doping components, and adopts a hierarchical doping design with large-radius La³⁺ replacing Zr sites and small-radius Y³⁺ filling lithium interstitial sites. The large-radius rare earth expands the free volume of the unit cell and suppresses lattice shrinkage and collapse at extremely low temperatures of -60℃; the small-radius rare earth balances the internal stress of the unit cell and avoids lattice microcracks caused by thermal cycling.
[0040] The general formula of the composite solid electrolyte is:
[0041] Li 7+δ La x Y y Zr 2-x-y La3O 12 -Li3Cl6;
[0042] Among them, x=0.08~0.15, y=0.04~0.09, δ=0.12~0.25.
[0043] The cubic phase LLZO oxide and rare earth chlorine halides are used as the composite matrix in a mass ratio of 7:3; the LLZO particle size D50 is 1.6 μm, the halide particle size D50 is 1.0 μm, and the matrix has its own three-dimensional octahedral lithium-ion transport lattice channel.
[0044] Optionally, the dual rare earth doped modification components include lanthanum rare earth salts and yttrium rare earth salts.
[0045] In one embodiment, the dual rare earth doping components are lanthanum nitrate monohydrate La(NO3)3·H2O and yttrium nitrate trihydrate Y(NO3)3·3H2O, which are 99.99% pure rare earth salts; the La³⁺ ion radius is 103 pm and the Y³⁺ ion radius is 89 pm, thereby achieving differential substitution of large and small ion sites.
[0046] As a further optimization of the technical solution of this application, the composite solid electrolyte also includes a charge-compensating lithium source, which is used to compensate for the negative lattice charge generated by rare earth anisovalent substitution, replenish free lithium ions, and increase the carrier concentration.
[0047] In one embodiment, the charge-compensating lithium source is anhydrous LiNO3 with a purity of 99.95%.
[0048] As a further optimization of the technical solution of this application, the composite solid electrolyte also contains a trace amount of sintering modifier to reduce the annealing temperature and assist rare earth elements in uniformly embedding into the crystal lattice.
[0049] In one embodiment, the sintering modifier is nano-Al2O3, with a doping amount of 1.2 wt% of the total matrix mass.
[0050] As a preferred embodiment of the present invention, in the composite solid electrolyte, x=0.12, y=0.06, δ=0.18, which is the optimal doping ratio for all operating conditions.
[0051] See Figure 1 The rare-earth dual-doped modified composite solid electrolyte provided by the invention employs synergistic doping at differentiated rare-earth sites to precisely replace the matrix Zr. 4 ⁺ and Li⁺ lattice sites, hierarchical control of cell volume, and directional construction of controllable lithium vacancies.
[0052] La³⁺ large radius rare earth doping sites: directional substitution of Zr lattice 4 The ⁺ site occupies the central position of the octahedron in the unit cell, expands the free volume of the unit cell lattice, suppresses low-temperature lattice shrinkage distortion, widens the lithium-ion transition channel, and reduces the low-temperature lattice deformation resistance.
[0053] Y³⁺ small radius rare earth doping sites: directionally replace interstitial Li⁺ sites in the crystal lattice, fill vacancy in the crystal lattice, finely regulate intracellular stress, eliminate microcracks in the lattice after doping, passivate grain boundary activity, and inhibit the formation of the LiCl insulating passivation layer on the negative electrode.
[0054] Lithium compensation coordination relationship: compensates for the enrichment of Li⁺ around rare earth substitution sites, balances the valence charge difference, eliminates lattice charge recombination centers, avoids lithium ions being captured by defect sites, and ensures that ions can migrate freely.
[0055] Grain boundary bonding: No segregation of rare earth elements, more than 94% of rare earth elements are embedded in the crystal lattice, with only trace amounts enriched at the grain boundaries, optimizing the grain boundary bonding force, reducing the grain boundary impedance, and preventing the formation of rare earth inert oxide impurities.
[0056] Combination Figure 1 The rare earth dual-doped modified composite solid electrolyte provided by the present invention has a dense polycrystalline composite structure with a grain size of 0.8~1.2μm and an overall porosity of ≤3.2%; the grains are tightly bonded and the grain boundaries are continuously connected; after dual rare earth doping, the lattice defects are controllable and the number of lithium vacancies in the lattice is increased to 2.7 times that of the pure phase matrix.
[0057] The rare-earth dual-doped modified composite solid electrolyte provided by this invention relies on the modification to broaden the cell channels and grain boundaries for dual-pathway lithium conduction. The rare earth weakens the Li-O and Li-Cl bond forces, reducing the lithium-ion insertion / extraction energy barrier. La³⁺ supports the lattice, preventing cell shrinkage and closure. Pre-set rare-earth artificial lithium vacancies continuously conduct lithium ions, unrestricted by polymer chain segment and native lattice contraction, ensuring long-term low-temperature ion migration. The electrolyte has an electronic conductivity ≤7.2×10⁻¹²S / cm, providing full-domain electronic insulation and allowing only vertical lithium-ion migration, thus blocking the lithium dendrite electronic growth pathway.
[0058] The rare-earth dual-doped modified composite solid electrolyte provided by the present invention, when attached to the lithium metal anode side, uses Y³⁺ to passivate the grain boundary reduction activity, block the side reaction between halide components and lithium anode, and suppress the lateral growth of lithium dendrites; when attached to the high-voltage cathode side, uses La³⁺ to enhance the lattice oxidation resistance, widen the electrochemical window to 4.9V, resist the oxidation corrosion of the high-nickel cathode interface, and reduce the degree of space charge layer distortion at the cathode interface.
[0059] The rare-earth dual-doped modified composite solid electrolyte provided by the present invention has the following core properties:
[0060] Ionic conductivity: ≥4.1 mS / cm at 25℃; ≥0.31 mS / cm at -40℃; ≥0.072 mS / cm at -60℃;
[0061] Mechanical properties: Young's modulus 2.4 GPa, compressive strength 118 MPa, excellent resistance to dendrite penetration;
[0062] Electrochemical window: 0.45V~4.90V;
[0063] Interface performance: The interface impedance of the lithium symmetric battery at room temperature is ≤152Ω, and the impedance fluctuation after 1200h cycling at -60℃ is ≤7%;
[0064] Structural stability: No phase transformation at 65~720℃, no lattice cracking or rare earth precipitation after repeated thermal cycling at -60℃.
[0065] In addition, the present invention provides a method for preparing the above-mentioned rare earth dual-doped modified composite solid electrolyte, comprising the following steps:
[0066] The ceramic inorganic matrix is vacuum activated to obtain an activated matrix, which is used to remove adsorbed crystal water and oxygen-containing impurities on the surface of the powder, and to avoid the formation of inert impurity phases of rare earth hydroxides during subsequent rare earth doping; wherein, the ceramic inorganic matrix is a cubic phase LLZO oxide and rare earth chloride halide composite matrix.
[0067] The activated matrix is immersed in a rare earth impregnation solution for mechanical predoping to obtain a predoped intermediate. By relying on mechanical shear force, rare earth ions are pre-extruded into the lattice sites on the surface of the matrix to achieve pre-substitution, reduce the activation energy of subsequent annealing doping, and improve the utilization rate of rare earth doping. The rare earth impregnation solution contains lanthanum rare earth salt, yttrium rare earth salt and charge-compensated lithium source, and the molar ratio of lanthanum rare earth salt and yttrium rare earth salt is (0.08~0.15):(0.04~0.09).
[0068] The pre-doped intermediate was subjected to low-temperature spray drying to obtain the doped precursor powder;
[0069] The above-mentioned doped precursor powder was subjected to three-stage gradient low-temperature annealing to obtain annealed doped powder; wherein the three-stage gradient low-temperature annealing was gradually increased from 320℃ to 720℃.
[0070] In the method of the present invention, the peak annealing temperature of the three-stage gradient low-temperature annealing is adjustable from 680 to 720°C, and the holding time of each stage fluctuates by ±30 minutes.
[0071] Optionally, the rare earth impregnation solution may also contain nano-alumina, with the amount of nano-alumina added being 1.0~1.5 wt% of the ceramic inorganic matrix.
[0072] As a preferred embodiment of the present invention, the three-stage gradient low-temperature annealing includes:
[0073] The first stage of solvent removal and crystallization involves heating at a rate of 2℃ / min until reaching 320℃, then holding at that temperature for 90min to completely remove the methanol solvent, solidify the rare earth ion coordination structure, complete the La and Y dual rare earth directional substitution of Zr and Li lattice sites, and complete the charge-replenishing lithium coordination.
[0074] The second stage involves lattice substitution doping, with a heating rate of 1.2℃ / min, reaching 560℃, and holding at that temperature for 130min.
[0075] The third stage of defect latching annealing involves a heating rate of 0.8℃ / min, reaching 720℃, and holding at that temperature for 160min to stabilize the doped lattice, close residual lattice defects, latch artificial lithium vacancies, and then naturally cool down to room temperature with the furnace.
[0076] Optionally, the annealed doped powder can be subjected to dry constant pressure molding, with a molding pressure of 22~30MPa and a holding pressure of 5~12min to obtain an electrolyte sheet; no high-temperature secondary sintering is required, and the sheet does not crack after molding and has extremely low porosity.
[0077] Optionally, the process may also include: subjecting the electrolyte sheet to low-temperature interface passivation post-treatment to eliminate stress within the compression lattice and passivate the activity of the electrolyte's two-sided interface.
[0078] In the method of this invention, firstly, molecular-level mixing of two rare earth elements and a lithium source is achieved through liquid phase, and then mechanical force is used to pre-embed the lithium into the lattice to reduce the energy barrier of the doping reaction. Relying on three-stage gradient low-temperature annealing, solvent removal, site substitution, and defect locking are completed in a time-sharing and step-by-step manner to achieve site-specific doping of different rare earth elements in the lattice. The lithium source is compensated to simultaneously balance the lattice charge and eliminate the defect lithium capture effect. The entire process is carried out at low temperature to avoid problems such as precipitation of rare earth oxide impurities, high-temperature hydrolysis of halides, and excessive lattice sintering. Finally, a rare earth modified lattice structure with controllable vacancies, stable grain boundaries, and wide-temperature lithium conductivity is constructed, which simultaneously improves the electrolyte's conductivity, mechanical properties, and interface compatibility.
[0079] Specifically, the conditions for low-temperature interface passivation post-treatment are an argon atmosphere and a constant temperature of 60°C for 7 hours.
[0080] The rare-earth dual-doped modified composite solid electrolyte of this application will be further described below with reference to specific embodiments.
[0081] Unless otherwise specified, the main components involved in the following embodiments of this application are all purchased from commercially available products.
[0082] Example 1
[0083] The rare-earth dual-doped modified composite solid electrolyte of the present invention is prepared according to the following steps:
[0084] (1) Matrix activation
[0085] 70g of LLZO powder and 30g of rare earth chlorine halide powder were mixed in a mass ratio of 7:3 and dried in a vacuum oven at 62℃ for 12h with a vacuum degree of -0.096MPa to obtain the activated matrix.
[0086] (2) Mechanical predoping
[0087] Using anhydrous methanol as the dispersion solvent and with a water content ≤8ppm, 0.92g of La(NO3)3·H2O, 0.38g of Y(NO3)3·3H2O, 0.64g of anhydrous LiNO3, and 1.2g of nano-alumina were added, with the addition amount being 1.15wt% of the ceramic inorganic matrix mass. The mixture was magnetically stirred for 4h at a stirring speed of 280r / min in an argon-sealed environment at a constant temperature of 38℃ to prepare a rare earth impregnation solution with a solid-liquid mass ratio of 1:5.
[0088] La(NO3)3·H2O and Y(NO3)3·3H2O are high-purity rare earth salts of 99.99%, and anhydrous LiNO3 has a purity of 99.95%.
[0089] The activated matrix powder was completely immersed in rare earth impregnation solution and placed in a planetary ball mill jar to obtain a pre-doped intermediate.
[0090] Ball milling parameters: zirconia grinding balls, ball-to-material ratio 8:1, rotation speed 420 r / min, segmented ball milling for a total of 5.5 h; forward ball milling 2 h + intermittent standing for 30 min + reverse ball milling 3 h.
[0091] (3) Low-temperature spray drying
[0092] The pre-doped intermediate was spray-dried at low temperature using a spray dryer to prepare the doped precursor powder.
[0093] Drying process: Inlet temperature 75℃, outlet temperature 42℃, feed rate 12mL / min, argon carrier gas atomization.
[0094] The doped precursor powder has a uniform particle size of D50=1.3μm, with rare earth elements uniformly distributed at the nanoscale and without agglomeration or segregation.
[0095] (4) Three-stage gradient low-temperature annealing
[0096] The doped precursor powder is transferred into a segmented temperature-controlled tubular annealing furnace. The tubular furnace is protected by an argon atmosphere, ensuring an oxygen-free environment and preventing oxidation throughout the process. The temperature is raised and held in stages, with a maximum annealing temperature of 720℃, thus preventing the precipitation of impurities from rare earth at high temperatures.
[0097] First stage of solvent removal and crystallization: heating rate 2℃ / min, heating to 320℃, holding at a constant temperature for 90min, completely removing methanol solvent, and solidifying rare earth ion coordination structure;
[0098] The second stage of lattice substitution doping: heating rate 1.2℃ / min, heating to 560℃, holding at a constant temperature for 130min, completing the La and Y dual rare earth directional substitution of Zr and Li lattice sites, and completing the charge-replenishing lithium coordination;
[0099] The third stage of defect latching annealing: heating rate 0.8℃ / min, heating to 720℃, holding at a constant temperature for 160min, stabilizing the doped lattice, closing residual lattice defects, latching artificial lithium vacancies, and naturally cooling to room temperature with the furnace.
[0100] (5) Dry constant pressure molding
[0101] Weigh the annealed doped powder, press it into tablets using a mold, press it at a pressure of 26 MPa, hold it at the pressure for 8 min, and prepare a dense electrolyte tablet with a thickness of 110 μm.
[0102] (6) Low-temperature interface passivation post-treatment
[0103] Under an argon atmosphere, the electrolyte was kept at a constant temperature of 60℃ for 7 hours to eliminate the internal stress of the crystal lattice during pressing, passivate the activity of the electrolyte's two-sided interface, and then discharged and cut to obtain the rare earth-doped modified composite solid electrolyte product. Figure 2 This is a comprehensive microscopic characterization diagram of the finished product. In this embodiment, x=0.12, y=0.06, and δ=0.18.
[0104] Example 2
[0105] The difference between this embodiment and Example 1 lies in the amount of LLZO powder, rare earth chlorohalide powder, La(NO3)3·H2O, Y(NO3)3·3H2O, and anhydrous LiNO3. The amounts of the remaining components and process parameters remain unchanged.
[0106] LLZO powder weighs 70g;
[0107] Rare earth chlorine halide powder: 30g;
[0108] La(NO3)3·H2O is 0.92g;
[0109] Y(NO3)3·3H2O is 0.38g;
[0110] The amount of anhydrous LiNO3 was 0.64 g.
[0111] In this embodiment, x=0.08, y=0.04, and δ=0.12.
[0112] Example 3
[0113] The difference between this embodiment and Example 1 lies in the amount of LLZO powder, rare earth chlorohalide powder, La(NO3)3·H2O, Y(NO3)3·3H2O, and anhydrous LiNO3. The amounts of the remaining components and process parameters remain unchanged.
[0114] LLZO powder weighs 70g;
[0115] Rare earth chlorine halide powder: 30g;
[0116] The amount of La(NO3)3·H2O is 1.171g;
[0117] Y(NO3)3·3H2O is 0.86g;
[0118] The amount of anhydrous LiNO3 was 1.33 g.
[0119] In this embodiment, x=0.15, y=0.09, and δ=0.25.
[0120] Example 4
[0121] The difference between this embodiment and Embodiment 1 is that it does not contain anhydrous LiNO3, while the amounts of other components and process parameters remain unchanged.
[0122] Example 5
[0123] The difference between this embodiment and Embodiment 1 is that it does not contain nano-alumina, while the amounts of other components and process parameters remain unchanged.
[0124] Example 6
[0125] The difference between this embodiment and Embodiment 1 is that LLZO powder and rare earth chlorine halide powder are mixed in a mass ratio of 6:4.
[0126] Example 7
[0127] The difference between this embodiment and Embodiment 1 is that LLZO powder and rare earth chlorine halide powder are mixed in a mass ratio of 8:2.
[0128] Comparative Example 1
[0129] The difference between this embodiment and Embodiment 1 is that it does not contain rare earth chloro halides.
[0130] Comparative Example 2
[0131] The difference between this embodiment and Embodiment 1 is that the solid electrolyte is prepared using a traditional high-temperature solid-phase disordered doping process.
[0132] The following steps are included: The difference between this embodiment and Example 1 is that the solid electrolyte is prepared by the traditional high temperature solid phase disordered doping process, without liquid phase predoping and low temperature gradient annealing process. The steps are as follows: (1) Dry mixing of powder: 70g of LLZO powder and 30g of rare earth chlorine halide powder are physically dry mixed, and the corresponding amounts of La (NO3)3·H2O, Y (NO3)3·3H2O, anhydrous LiNO3 and nano Al2O3 are directly added. The powder is ball-milled with anhydrous ethanol for 8h; (2) High temperature pre-calcination: The dried powder is transferred to a corundum crucible and pre-calcined at 950℃ in air atmosphere for 6h with a heating rate of 5℃ / min; (3) Secondary grinding: The pre-calcined product is ball-milled again to refine the powder; (4) High temperature sintering and forming: The powder is dry-pressed into 110μm sheets at 30MPa and sintered at 1080℃ for 12h; (5) No low temperature interface passivation is performed, and the comparative sample is obtained by natural cooling; The entire process is carried out without argon protection or liquid phase impregnation for fixed-point doping, and rare earth ions are randomly and disorderedly distributed in the crystal lattice.
[0133] The solid electrolytes of all the above embodiments and comparative examples were subjected to performance tests, and the test standards in Table 1 were used respectively.
[0134] Table 1:
[0135] Testing items Test equipment Test methods Reference Standard Ionic conductivity at 25℃ Impedance analyzer Electrochemical impedance spectroscopy (EIS) ASTM E1876 -40℃ Ionic conductivity Electrochemical workstation + high and low temperature environmental chamber (-70~150℃) EIS test after 2-4 hours of constant temperature ASTM E1876 -60℃ Ion conductivity Electrochemical workstation + liquid nitrogen refrigeration cryogenic testing system Low temperature impedance testing General methods of literature review Young's modulus Nanoindentation instrument Compressive stress-strain curve ASTM E2546 compressive strength Electronic universal testing machine Uniaxial compression ASTM C1424 Dendrite puncture resistance Electrochemical workstation Critical Current Density (CCD) Test Document Standards Electrochemical window Electrochemical workstation Linear scanning voltammetry ASTM G102 Lithium-ion symmetric cell interfacial impedance Electrochemical workstation Li|SSE|Li Impedance Spectroscopy (EIS) General literature Impedance fluctuation after cycling at -60℃ for 1200 hours Battery testing system + low temperature chamber Long-term constant current circulation + periodic EIS IEC62660 Does a phase transition occur at 65~720℃? XRD + High-Temperature Furnace; In-Situ High-Temperature XRD High temperature XRD ASTM E975 Does the -60℃ thermal cycling cause lattice cracking? SEM Cracks were observed before and after thermal cycling. ASTM E2905 Rare earth precipitation SEM-EDS Elemental surface scan, line scan ASTM E1508
[0136] The test results of all the above embodiments and comparative examples are shown in Tables 2-1 and 2-2.
[0137] Table 2-1:
[0138] Testing items Example 1 Example 2 Example 3 Example 4 Example 5 Ionic conductivity at 25℃ (mS / cm) 4.07 3.05 3.42 1.81 3.43 Ionic conductivity at -40℃ (mS / cm) 0.313 0.221 0.256 0.102 0.261 Ionic conductivity at -60℃ (mS / cm) 0.074 0.047 0.060 0.016 0.054 Young's modulus (GPa) 2.42 2.14 2.28 1.60 2.03 Compressive strength (MPa) 116 104 112 74 99 Dendrite puncture resistance mA / cm² CCD=0.61 CCD=0.44 CCD=0.53 CCD=0.27 CCD=0.48 Electrochemical window (V) 0.45~4.90 0.48~4.76 0.46~4.83 0.52~4.51 0.47~4.79 Interfacial impedance (Ω) of lithium-ion symmetric batteries 156 227 169 410 205 Impedance fluctuation (%) after cycling at -60℃ for 1200h 6.4 11.1 9.5 31.7 13.7 Does a phase transition occur at 65~720℃? No phase transition No phase transition No phase transition slight lattice distortion No phase transition Does the -60℃ thermal cycling cause lattice cracking? No cracks A small number of nanopores No cracks Numerous through cracks A few microcracks Rare earth precipitation No impurities, with trace grain boundary dispersion Trace grain boundary enrichment Trace grain boundary enrichment <![CDATA[A large amount of La₂O₃ impurity phase precipitates]]> Local rare earth agglomeration
[0139] Table 2-2:
[0140] Testing items Example 6 Example 7 Comparative Example 1 Comparative Example 2 Ionic conductivity at 25℃ (mS / cm) 3.65 3.22 1.24 1.52 Ionic conductivity at -40℃ (mS / cm) 0.281 0.201 0.041 0.068 Ionic conductivity at -60℃ (mS / cm) 0.062 0.041 0.005 0.013 Young's modulus (GPa) 2.21 2.30 1.88 1.73 Compressive strength (MPa) 107 115 82 79 Dendrite puncture resistance 0.57 0.53 0.23 0.26 Electrochemical window (V) 0.46-4.85 0.45-4.88 0.52-4.33 0.52-4.45 Interfacial impedance (Ω) of lithium-ion symmetric batteries 171 198 570 762 Impedance fluctuation (%) after cycling at -60℃ for 1200h 8.9 10.3 45.1 37.2 Does a phase transition occur at 65~720℃? No phase transition No phase transition 620℃ cubic to tetragonal phase transition 590℃ Slightly Distorted Phase Transition Does the -60℃ thermal cycling cause lattice cracking? Micro-nanopores No obvious cracks Large-scale collapse and cracking Through-the-area crack Rare earth precipitation Trace grain boundary enrichment Trace grain boundary enrichment without rare earth doping <![CDATA[a large amount of Y2O3 and La2Zr2O7 impurity phases]]>
[0141] Results analysis:
[0142] 1. Through comparative examples 1 to 3, the matching of the dual rare earth doping range was verified. In example 1, the optimal ratio of x=0.12, y=0.06, and δ=0.18 was found to be optimal, exhibiting the best high and low temperature ionic conductivity, mechanical strength, and interface stability. In example 2, insufficient cell expansion at low doping levels led to shrinkage of the low-temperature channels, resulting in a simultaneous decline in conductivity and mechanical properties. In example 3, at the upper limit of doping levels, stress accumulation occurred in the crystal structure, leading to a slight increase in interface impedance. This demonstrates that the present invention limits the effective doping window to x=0.08~0.15, y=0.04~0.09, and δ=0.12~0.25, with the intermediate ratio showing the best overall performance.
[0143] 2. By comparing Examples 1 and 4, the necessity of a charge-compensated lithium source was verified. After removing the charge-compensating component of anhydrous LiNO3, the charge defects caused by lattice heterovalent substitution could not be neutralized, and a large number of free lithium ions were captured by the defects. The conductivity at room temperature was only 1.91 mS / cm, and the conductivity at -60℃ was as low as 0.017 mS / cm. The interfacial impedance of the symmetric cell increased to 426 Ω, and the impedance fluctuation at low temperature long-cycle exceeded 30%. Through-cracks were generated during thermal cycling. This indicates that a matching lithium source with charge compensation is a necessary component to increase the lithium vacancy concentration and eliminate ion capture defects.
[0144] 3. By comparing Example 1 and Example 5, the sintering aid effect of nano-alumina was verified. After removing nano-Al2O3, rare earth ions are prone to local agglomeration, the grain boundary bonding strength decreases, the compressive strength and dendrite resistance decrease, and the low-temperature cycling impedance fluctuation increases to 13.5%. Nano-alumina can reduce the annealing activation energy, promote the uniform and fixed-point insertion of rare earth into the lattice, and optimize the grain boundary bonding strength.
[0145] 4. Through Comparative Examples 1, 6, 7, and 1, the matrix ratio of LLZO-rare earth halide composite was verified. In Example 6, the halide content was increased to 40%, resulting in a slight increase in low-temperature conductivity, but the electrochemical window narrowed and the stability of the high-voltage cathode decreased. In Example 7, the halide content was only 20%, resulting in insufficient low-temperature lithium-ion conduction channels and significant low-temperature performance degradation. In Comparative Example 1, the pure LLZO system without halide had a conductivity of only 0.006 mS at -60℃, and an irreversible cubic-tetragonal phase transition occurred at 620℃, with the low-temperature lattice directly collapsing and cracking. The 7:3 composite ratio can simultaneously balance ultra-low temperature conductivity and high-voltage electrochemical stability, which is the optimal matrix ratio of this invention.
[0146] 5. Through Comparative Examples 1 and 2, the low-temperature gradient process of the present invention, compared with the traditional high-temperature disordered solid-phase doping process, has multiple defects: high-temperature sintering at 1080℃ leads to rare earth ion segregation, generating inert impurities such as Y2O3 and La2Zr2O7 that block ion channels; there is no fixed-point doping mechanism, making it impossible to simultaneously expand the unit cell and balance lattice stress; thermal cycling results in widespread through-cracks; and the high and low temperature conductivity is only about 1 / 3 of that of the present invention; moreover, the high-temperature environment damages the halide composition, resulting in extremely poor interphase bonding. The present invention uses liquid-phase pre-doping and 720℃ three-stage low-temperature gradient annealing to achieve La³⁺ fixed-point substitution of Zr sites and Y³⁺ filling of lithium interstitials, without impurity phase precipitation, thus solving the problems of low-temperature lattice shrinkage cracking and ion conduction cliff from the microscopic root.
[0147] In summary, this invention utilizes a comprehensive and synergistic approach involving differentiated, site-specific dual rare-earth doping with large-radius La³⁺ and small-radius Y³⁺ elements, a charge-compensated lithium source, an LLZO-rare-earth chloride-halide 7:3 composite matrix, and a three-stage low-temperature gradient annealing process to prepare a dense polycrystalline composite solid-state electrolyte. The electrolyte exhibits a grain size of 0.8–1.2 μm, a porosity ≤3.2%, and a lattice lithium vacancy rate 2.7 times higher than that of a pure-phase matrix. It can operate stably over a wide temperature range of -60℃ to 720℃, and possesses advantages such as high ionic conductivity, high mechanical dendrite strength, a wide electrochemical window of 0.45–4.9V, extremely low interfacial impedance, and no cracking during thermal cycling. This makes it suitable for mass production of all-solid-state lithium metal batteries for extreme applications such as high-altitude automotive, polar energy storage, and aerospace.
[0148] The above are all preferred embodiments of this application, and are not intended to limit the scope of protection of this application. All equivalent changes and simple substitutions made based on the structure, composition and preparation principle of this application should be covered within the scope of protection of the claims of this application.
[0149] The above are all preferred embodiments of this application, and are not intended to limit the scope of protection of this application. Therefore, all equivalent changes made in accordance with the structure, shape and principle of this application should be covered within the scope of protection of this application.
Claims
1. A rare-earth dual-doped modified composite solid electrolyte, characterized in that, The general formula for the solid electrolyte is: Li 7+δ La x Y y Zr 2-x-y La3O 12 -Li3Cl6; Among them, x=0.08~0.15, y=0.04~0.09, δ=0.12~0.
25.
2. The rare-earth dual-doped modified composite solid electrolyte according to claim 1, characterized in that, x=0.12, y=0.06, δ=0.
18.
3. The rare-earth dual-doped modified composite solid electrolyte according to claim 1, characterized in that, The solid electrolyte comprises a ceramic inorganic matrix, a dual rare earth doped modified component, and a charge-compensating lithium source. The ceramic inorganic matrix is a cubic phase LLZO oxide and rare earth chloride halide composite matrix, and the dual rare earth doped modified component comprises lanthanum rare earth salt and yttrium rare earth salt.
4. The rare-earth dual-doped modified composite solid electrolyte according to claim 3, characterized in that, The solid electrolyte also includes nano-alumina.
5. The rare-earth dual-doped modified composite solid electrolyte according to claim 1, characterized in that, In the ceramic inorganic matrix, the mass ratio of cubic LLZO oxide to rare earth chloride halide is 7:
3.
6. A method for preparing a rare-earth dual-doped modified composite solid electrolyte, characterized in that, Includes the following steps: A ceramic inorganic matrix is vacuum activated to obtain an activated matrix; wherein the ceramic inorganic matrix is a cubic phase LLZO oxide and rare earth chloride halide composite matrix; The activated matrix is immersed in a rare earth impregnation solution for mechanical predoping to obtain a predoped intermediate; wherein the rare earth impregnation solution contains lanthanum rare earth salt, yttrium rare earth salt and charge-compensating lithium source; The pre-doped intermediate was subjected to low-temperature spray drying to obtain the doped precursor powder; The above-mentioned doped precursor powder was subjected to three-stage gradient low-temperature annealing to obtain annealed doped powder; wherein the three-stage gradient low-temperature annealing was gradually increased from 320℃ to 720℃.
7. The method for preparing a rare-earth dual-doped modified composite solid electrolyte according to claim 6, characterized in that, The rare earth impregnation solution also contains nano-alumina.
8. The method for preparing a rare-earth dual-doped modified composite solid electrolyte according to claim 6, characterized in that, The three-stage gradient low-temperature annealing includes: The first stage involves a heating rate of 2℃ / min, raising the temperature to 320℃ and holding it at that temperature for 90 minutes. The second stage involves a heating rate of 1.2℃ / min, raising the temperature to 560℃, and holding the temperature for 130 minutes. The third stage involves a heating rate of 0.8℃ / min, raising the temperature to 720℃, and then maintaining that temperature for 160 minutes.
9. The method for preparing a rare-earth dual-doped modified composite solid electrolyte according to claim 6, characterized in that, Also includes: The annealed doped powder is then subjected to dry constant pressure molding to obtain an electrolyte sheet.
10. The method for preparing a rare-earth dual-doped modified composite solid electrolyte according to claim 9, characterized in that, Also includes: The electrolyte sheet is subjected to low-temperature interface passivation post-treatment.